2006
DOI: 10.1111/j.1365-2036.2006.00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori eradication prevents the development of gastric cancer – results of a long‐term retrospective study in Japan

Abstract: SUMMARY AimThis large-scale study was designed to investigate the incidence of gastric cancer after Helicobacter pylori (H. pylori) eradication in Japan. MethodsThis study was a retrospective multicentre study performed at 23 centres in Japan. Patients in whom H. pylori had been successfully eradicated and those in whom the infection persisted were entered into the study if they had undergone an upper endoscopic examination at least once a year for five consecutive years. The incidence rates of gastric cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…However, it is necessary to investigate more cases because of too few patients followed up during long term. Since the annual incidence of gastric cancer in H. pylori -positive patients was reported to be 0.38–0.5% [4, 33], after ESD, patients have a higher risk of developing gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is necessary to investigate more cases because of too few patients followed up during long term. Since the annual incidence of gastric cancer in H. pylori -positive patients was reported to be 0.38–0.5% [4, 33], after ESD, patients have a higher risk of developing gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There have been few reports of the occurrence of metachronous cancer after endoscopic treatment [11,12]. Kato et al [5] reported that eradication of H. pylori after endoscopic resection of EGC reduced the risk of development of metachronous gastric cancer. We report a retrospective study of the factors associated with metachronous gastric cancer that developed after endoscopic treatment of EGC.…”
Section: Introductionmentioning
confidence: 98%
“…Gastric cancer carcinogenesis is a multifactorial process related to an interaction of host factors, Helicobacter pylori infection and environmental factors such as diet [5][6][7][8]. Correa and Miller [9] proposed a precancerous cascade in which the gastric mucosa undergoes a series of changes beginning with gastritis, followed by atrophy often with intestinal metaplasia, followed by dysplasia and eventually gastric cancer [10].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond this point, despite H. pylori eradication, inflammation in the stomach persists. Accordingly, amelioration of the gastric inflammation rather than simple eradication of the pathogen is generally accepted to be the key to cancer prevention [13]. This implies that chronic gastritis has a greater chance of leading to gastric cancer than infection by H. pylori alone.…”
Section: A Cross-link Between H Pylori-associated Cag and Gastric Camentioning
confidence: 99%
“…Although two recent large-scale, prospective studies, both performed in a population at high risk for gastric cancer, confirmed H. pylori infection as a definite risk factor for the development of gastric cancer [3,34], the opposite premise, that the eradication of H. pylori infection is an appropriate target for the prevention of gastric cancer, has yet to be confirmed and remains controversial [35,36]. Three randomized, placebo-controlled trials performed in China and Columbia found no significant protective effect following H. pylori eradication [35][36][37], whereas three recently published Japanese studies [10,13,38] reported that H. pylori eradication prevents the development of gastric cancer significantly, even in patients with precancerous gastric lesions. However, these observations did not address the possibility that earlier eradication therapy or other, similar types of intervention aimed at reducing gastric inflammation could be beneficial in high-risk populations [39].…”
Section: Preventing Precancerous Atrophic Gastritis: Is It Possible Amentioning
confidence: 99%